1988
DOI: 10.1002/hlca.19880710127
|View full text |Cite
|
Sign up to set email alerts
|

Synthese von Dimethyl‐4a,8a‐methanophthalazin‐1,4‐dicarboxylat und Derivaten

Abstract: Synthesis of Dimethyl 4a,Sa-Methanophthalazine-1,4-dicarboxylate and DerivativesDiels-Alder reaction with inversed electron demand of 123-cyclopropabenzol 1 with dimethyl 1,2,4,5-tetrazine-3,6-dicarboxylate (2) yields dimethyl-4a,8a-methanophthalazine-1,4-dicarboxylate (3). The reactions of 3 with nucleophiles are also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 11 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Its 1,2 double bond is to a large extent isolated from other π-electron systems, and is unique for its aliphatic character. The other two aromatic bonds (3,4 and 4,5see insert in Table ) can also function as diene in some [4 + 2] cycloadditions. Recent studies have also shown that the π bonds of the aromatic ring can react as dienophile. , The length of the three double bonds in the acenaphthylene molecule is in the sequence C1−C2 (1.36 Å) < C4−C5 (1.38 Å) < C3−C4 (1.43 Å), and the bond order is reversed, C1−C2 (1.83) > C4−C5 (1.72) > C3−C4 (1.18) (see Table ). The bond order was predicted by using the AIM feature in Gaussian based on the theory of atoms in molecules developed by Bader and co-workers, which defines chemical properties on the basis of the topology of the electron density.…”
Section: Resultsmentioning
confidence: 99%
“…Its 1,2 double bond is to a large extent isolated from other π-electron systems, and is unique for its aliphatic character. The other two aromatic bonds (3,4 and 4,5see insert in Table ) can also function as diene in some [4 + 2] cycloadditions. Recent studies have also shown that the π bonds of the aromatic ring can react as dienophile. , The length of the three double bonds in the acenaphthylene molecule is in the sequence C1−C2 (1.36 Å) < C4−C5 (1.38 Å) < C3−C4 (1.43 Å), and the bond order is reversed, C1−C2 (1.83) > C4−C5 (1.72) > C3−C4 (1.18) (see Table ). The bond order was predicted by using the AIM feature in Gaussian based on the theory of atoms in molecules developed by Bader and co-workers, which defines chemical properties on the basis of the topology of the electron density.…”
Section: Resultsmentioning
confidence: 99%
“…Strongly electron deficient triazines, e.g., R 1 -R 3 ) CO 2 Et, add under normal conditions but when less activated, e.g., R 1 ) R 2 ) H; R 3 ) CO 2 Et, highpressure conditions are required. In contrast, the addition of tetrazine dicarboxylate 242 or bis(trifluoromethyl)tetrazine leads to product 212 in the norcaradiene form. Indeed, 212 (R ) CF 3 ) has provided for subsequent significant synthetic chemistry in which the distinct electron-rich cyclohexadiene and electron deficient diazadiene moieties are utilized independently.…”
Section: In Cycloadditionsmentioning
confidence: 99%
“…222 In similar vein, R-pyrone provides methano- [10]annulene after loss of CO 2 . 197 Reactions with triazines 240,241 or tetrazines 242,243 likewise lead to addition-elimination, this time of dinitrogen. Addition of triazine gives a product is which the threemembered ring is opened, viz.…”
Section: In Cycloadditionsmentioning
confidence: 99%
“…128.1 (C16l2O), 128.6 (CI7/Ig), 128.8 (C3t6), 129.7 (ClDlt4 or Cl llI3),131.6 (Cl l/13 or c10/14), 13s.5 (c9), 138.7(8) (C2a or C6a), 138.8(1) (C6a or CZa), 139.0 (C15). Mass spectnrm (relative intensity): m/z (70 eV) 385 (16,Cz+FIr58rBr +1), 384 (63, CzallrssrBr), 382(57, Cz+FIrs7eBd,3a4 (10),303 (37, M-Br),302 (100, M-I{Br'),301 (18),300 (47)' 298 (10), l5l (19) r50 (197o).…”
Section: ' -( Phenylpenryiidene)-lh-cyclopropa[b] Naphthalene ( I I4n|mentioning
confidence: 99%